Andrew Marvell's Liminal Lyrics : the Space Between. - Faust, Joan (University of Delaware, 2012)
The work is an interdisciplinary study of the major lyric poems of 17th-century British metaphysical poet Andrew Marvell. It invites Marvell readers to view the poet and some of his representative lyrics in the context of the anthropological concept of liminality and the in-between aspects of experience. Utilizing multidisciplinary and multi-media contexts in a broad matrix of experience, the study would appeal to scholars in English history, English literature, early modern culture, sociology, psychology, visual arts, horticulture, lingui.